Exploring factors that determine the innovation of micro and small enterprises: The role of entrepreneurial attitude towards innovation in Woldia, Ethiopia - Erstu Tarko Kassa; Tilahun Getnet Mirete (Journal of Innovation and Entrepreneurship, 2022)
To transform micro and small enterprises to large companies, owners need to strive to launch new methods, systems, ways and innovations. Accordingly, innovation helps micro-enterprises to bounce to achieve fundamental change in their businesses. Micro and small enterprises are exposed by different factors to innovating new products and services. This study, therefore, focused on exploring factors that determine the innovation of service and manufacturing MSEs: the role of entrepreneurial attitude towards innovation in Woldia city administration. The researchers used a cross-sectional research design and followed a quantitative approach. The data were collected by using a structured questionnaire. The collected data were analysed by using SPSS v-25 and Amos graphics to conduct descriptive, factor, correlation, regression and path analysis. The study finding revealed that government support, access to infrastructure, entrepreneurial training, entrepreneurial attitude and the leadership of the owners significantly affected the innovation of service and manufacturing MSEs. Entrepreneurial training and leadership of the owners directly and indirectly affected the innovation of services and manufacturing MSEs through the mediating variable of entrepreneurial attitude.
Keywords: 650; Access to infrastructure; Attitude; Entrepreneurial training; Government support; Innovation; Leadership